THE IMPORTANCE OF INDEPENDENT WORK IN THE MODERN EDUCATIONAL PROCESS - Rakhmatova Nargiza Dolibaevna (Scholar Express Journal, 2023)
In this article, the author highlights the importance of independent learning in the professional training of future teachers of musical culture, students' self-control skills in musical hearing in independent learning, the principles of organizing independent learning.
Keywords: educational process; independent learning; competence